Loss Of The Role Of The Father Since Childhood: Trauma And Self-Defense Mechanisms In The Perspective Of Psychoanalytic Theory - Sagita, Auliyah Reski; Arianda, Arianda (International Journal of Asian Education, 2025)
Losing a father figure in childhood is an emotional experience that can have a significant impact on personality development, emotional stability, and social relationships until adulthood. In the perspective of psychoanalysis, this experience is understood as an initial trauma that affects the dynamics of the id, ego, and superego. This paper analyzes the loss of the father figure through the classical psychoanalytic approach of Sigmund Freud and contemporary thinkers such as Klein, Winnicott, and Bowlby. The method used is a literature study of developmental theories, object relations, attachments, and self-defense mechanisms. The results of the study show that the loss of a father can trigger basic anxiety, disturbances in emotional regulation, the use of self-defense mechanisms (repression, denial, displacement), and form a pattern of maladaptive interpersonal relationships. This trauma also affects parenting patterns in adulthood, such as hyperprotective tendencies as a form of emotional compensation. This study confirms the importance of psychodynamic interventions, parenting learning, and spiritual approaches to help individuals come to terms with past trauma and prevent the transmission of trauma between generations.